Development of Counseling Information System with Structured Analysis and Modeling in Object Oriented Approach - Agus Pamuji (Indonesian Scientific Journal, 2022)
The need and development of information systems continue to occur. The presence of an information system allows communication between users in counselling services. The development of information systems is a complex concept and has challenges in addition to problems. The main problem is that the requirements for the system are often not explained, making it difficult for designers and system analysts to understand, and adapt the design results to the needs of each user. The motivation of this research is to develop a counselling information system with an object-oriented approach. The method used in the development is the implementation of analysis and building a structured model with the output forming classes and their associations. The final result shows that the class that has been formed reduces the complexity of the system.